2021
DOI: 10.1101/2021.03.04.433942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The memory B cell response to influenza vaccination is impaired in older persons

Abstract: Influenza imparts an age-related increase in mortality and morbidity. The most effective countermeasure is vaccination; however, vaccines offer modest protection in older adults. To investigate how ageing impacts the memory B cell response we tracked haemagglutinin specific B cells by indexed flow sorting and single cell RNA sequencing in twenty healthy adults administered the trivalent influenza vaccine. We found age-related skewing in the memory B cell compartment six weeks after vaccination, with younger ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Memory B cell formation, which is another important output of the GC reaction, has also been shown to be impaired in older individuals. A recent study from our lab showed that there is impaired expansion of antigen-specific memory B cells in the peripheral blood of older adults post-influenza immunisation [79] . This age-related impairment in antigen-specific memory B cell formation was also observed after SARS-CoV-2 vaccination with mRNA-based vaccines [80] .…”
Section: How Vaccine-induced Humoral Immunity Is Generated and How It Changes With Agementioning
confidence: 87%
See 3 more Smart Citations
“…Memory B cell formation, which is another important output of the GC reaction, has also been shown to be impaired in older individuals. A recent study from our lab showed that there is impaired expansion of antigen-specific memory B cells in the peripheral blood of older adults post-influenza immunisation [79] . This age-related impairment in antigen-specific memory B cell formation was also observed after SARS-CoV-2 vaccination with mRNA-based vaccines [80] .…”
Section: How Vaccine-induced Humoral Immunity Is Generated and How It Changes With Agementioning
confidence: 87%
“…It has been proposed that ABCs represent a heterogenous population that can include plasma cell precursors, recently activated cells or recirculating memory B cells depending on context [202] , [203] , [204] , [205] . After seasonal influenza vaccination of younger and older people, the formation of haemagglutinin-specific memory B cells, including FCLR5+ atypical B cells, is impaired in older individuals [79] . This is despite the accumulation of ABCs with age, and thus it is likely that the increased frequency of ABCs with age represents the memory B cell pool acquired over the multiple immune challenges throughout the individual's lifetime, and that the formation of new vaccine-responsive ABCs is impaired during ageing.…”
Section: Mechanisms Underpinning the Age-related Decline Of The Gc Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In accordance, older adults are less likely to seroconvert against influenza viruses and generally have lower neutralizing antibody titers than younger adults [ 131 , 132 ]. Moreover, MBCs from elderly subjects are less likely to re-enter into GCs and further affinity mature against drifted variants [ 51 , 133 , 134 , 135 ]. Notably, GC B cells in elderly mice and humans are noted for their reduced expression of activation-induced cytidine deaminase (AID) [ 136 , 137 ], an enzyme critical for somatic hypermutation.…”
Section: Generation and Recall Of Humoral Immunity Against Iavsmentioning
confidence: 99%